Do we need new standards in dental implant testing? - Schneider Simon Matthias; Engleder Thomas; Schneider Robert; Haeger Andreas (Current Directions in Biomedical Engineering)
The ISO 14801 standard test is repeatedly criticized for not reflecting the actual conditions and loads realistically enough to which dental implants are exposed (e. g. during chewing). The aim of this paper is to provide a brief review of the test parameters of the ISO standard and to compare them critically with the parameters that prevail in vivo. The research revealed significant simplifications of the test conditions, wich can partly be justified with better reproducibility and comparability. Nevertheless, the realization remains that the test deviates considerably from real physiological loading conditions and should be adapted accordingly or supplemented by further tests.